Analysis of Millennial Generation Preferences Towards Brand Switching Decisions to Smartphone OPPO Brand in Jabodetabek - Melani Ali Selamat; Fauziah Eddyono (Dinasti International Journal of Education Management And Social Science, 2024)
Indonesia is one of the most smartphone-using countries in the world. Several smartphone brands, such as Samsung, Oppo, Xiaomi, Vivo, and Apple, dominate the Indonesian market share today.   From 2022 to March 2023, OPPO suddenly ranked first as the smartphone with the largest market share in Indonesia, rivaling several well-known smartphones, such as Samsung and Apple. This phenomenon needs to be analyzed further, especially on consumer preferences related to the decision to switch from a well-known smartphone to the OPPO brand, which is actually a newcomer to the smartphone market. This study aims to analyze consumer preferences in making switching decisions from various well-known smartphone brands to OPPO smartphone brands by utilizing conjoin analysis. The analysis was conducted on 204 millennial generation OPPO users in the Jabodetabek area. The results of the study show that product features are the most important attribute for consumers in making switching decisions, as evidenced by an importance value of 37.957, followed by marketing communication with an importance value of 28.589, price with an importance value of 12.048, brand image with an importance value of 11.249, and lifestyle with an importance value of 10.157. This research suggests that the development of product feature innovation is very important to win the smartphone market competition in Indonesia, especially in Jabodetabek.